2014
DOI: 10.3897/zookeys.428.7352
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Chiasmocleis (Microhylidae, Gastrophryninae) from the Atlantic Forest of Espírito Santo State, Brazil

Abstract: Among Neotropical microhylids, the genus Chiasmocleis is exceptionally diverse. Most species of Chiasmocleis were described in recent years based on external morphology, but recent studies using molecular data did not support the monophyly of the species groups clustered based on feet webbing. Furthermore, a phylogeographic study of C. lacrimae estimated high genetic divergence and low gene flow among populations across small geographic ranges. Increasing the molecular and geographic sampling, and incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 37 publications
3
13
0
5
Order By: Relevance
“…Total genomic DNA was extracted from ethanol-preserved liver or muscle tissues using Qiagen DNeasy kit (Valencia, CA, USA). We used the genetic matrix presented in Tonini, Forlani & de Sá (2014) , which included one of the new species; we also included samples of another new species as well as of C. alagoana and C. shudikarensis . Thus, the new dataset comprises samples of C. mantiqueira , C. leucosticta , C. alagoana , C. cordeiroi , C. crucis , C. schubarti , C. capixaba , C. lacrimae , C. quilombola , and the two Chiasmocleis species describe herein ( Appendix I ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total genomic DNA was extracted from ethanol-preserved liver or muscle tissues using Qiagen DNeasy kit (Valencia, CA, USA). We used the genetic matrix presented in Tonini, Forlani & de Sá (2014) , which included one of the new species; we also included samples of another new species as well as of C. alagoana and C. shudikarensis . Thus, the new dataset comprises samples of C. mantiqueira , C. leucosticta , C. alagoana , C. cordeiroi , C. crucis , C. schubarti , C. capixaba , C. lacrimae , C. quilombola , and the two Chiasmocleis species describe herein ( Appendix I ).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a phylogeographic analysis of C. lacrimae and C. capixaba recovered high genetic diversity and low gene flow among populations ( Tonini, Costa & Carnaval, 2013 ). Subsequent analyses, with an increased taxon and genetic sampling, recovered a new species, C. quilombola ( Tonini, Forlani & de Sá, 2014 ); moreover, the authors suggested the presence of an additional undescribed species.…”
Section: Introductionmentioning
confidence: 99%
“…Bittencourt-Silva & Silva (2013), on the other hand, referred to the species occurring in Ilha Grande as C. carvalhoi (now C. lacrimae; see Peloso et al, 2014). Tonini et al (2014), in a molecular phylogenetic analysis of the C. lacrimae and C. capixaba complexes, used DNA sequences of three specimens of Chiasmocleis from "Angra dos Reis, Rio de Janeiro" housed at the herpetological collection of the Universidade Federal Rural do Rio de Janeiro. Those specimens (RU 7003-05; referred as RN 7003-05 in Tonini et al, 2014) are actually from Ilha Grande, and are determined as Chiasmocleis gr.…”
Section: Amphibiamentioning
confidence: 99%
“…Tonini et al (2014), in a molecular phylogenetic analysis of the C. lacrimae and C. capixaba complexes, used DNA sequences of three specimens of Chiasmocleis from "Angra dos Reis, Rio de Janeiro" housed at the herpetological collection of the Universidade Federal Rural do Rio de Janeiro. Those specimens (RU 7003-05; referred as RN 7003-05 in Tonini et al, 2014) are actually from Ilha Grande, and are determined as Chiasmocleis gr. carvalhoi in that collection's catalog (curiously, they are not listed in the Appendix I of Bittencourt-Silva & Silva, 2013).…”
Section: Amphibiamentioning
confidence: 99%
“…The AF also seems to hold higher amphibian within-species genetic diversity in comparison to open areas, a pattern that is shared with two other tropical regions, Cuba and Madagascar (Rodríguez et al, 2015). Despite several decades of intensive studies on the AF, new species are still regularly discovered and named, while other well-established species are recognized as species complexes containing numerous candidate species that await formal description (Santana et al, 2012;Gehara et al, 2013Gehara et al, , 2014Condez et al, 2014;Lourenço-de-Moraes et al, 2014;Tonini et al, 2014;Ribeiro et al, 2015). This trend agrees with results from many other regions of the world where a routine application of molecular screening uncovers unprecedented levels of genetic diversity of amphibians, and integrative and molecular approaches lead to ever increasing rates of species description (Meegaskumbura et al, 2002;Stuart et al, 2006;Fouquet et al, 2007aFouquet et al, , 2007bVieites et al, 2009;Funk et al, 2012;Rowley et al, 2015).…”
mentioning
confidence: 99%